2020
DOI: 10.2106/jbjs.19.01499
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular Labral Reconstruction with Iliotibial Band Autograft

Abstract: Background: Labral reconstruction has been shown to result in improved patient-reported outcomes (PROs) at mid-term follow-up in patients with a deficient labrum. The purpose of this study was to determine survivorship and PROs at a minimum 10-year follow-up. Methods: A retrospective evaluation of a prospectively collected single-surgeon database included 91 hips (89 patients) that underwent arthroscopic labral reconstruction with iliotibial band autogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 20 publications
1
48
0
Order By: Relevance
“…Autologous ITB grafts have also been used in several other reconstruction procedures, including reconstruction of the anterior cruciate ligament (ACL), acetabular labral, superior J o u r n a l P r e -p r o o f capsule of the shoulder, and trauma-associated soft tissue defects. 5,12,13,17 Having documented their successful clinical outcomes, these studies further demonstrate the versatility of the ITB graft as a viable autologous material for tendon reconstruction. The potential morbidity associated with harvesting the autologous graft include wound infection, superficial phlebitis, seroma, muscle hernia, and deep vein thrombosis; however, these are rarely seen in practice.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 72%
See 1 more Smart Citation
“…Autologous ITB grafts have also been used in several other reconstruction procedures, including reconstruction of the anterior cruciate ligament (ACL), acetabular labral, superior J o u r n a l P r e -p r o o f capsule of the shoulder, and trauma-associated soft tissue defects. 5,12,13,17 Having documented their successful clinical outcomes, these studies further demonstrate the versatility of the ITB graft as a viable autologous material for tendon reconstruction. The potential morbidity associated with harvesting the autologous graft include wound infection, superficial phlebitis, seroma, muscle hernia, and deep vein thrombosis; however, these are rarely seen in practice.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 72%
“…13 Additionally, a case series dealing with acetabular labral reconstruction of 75 patients using ITB autografts observed no reported donor site complications, pain, or weakness. 17 Given the literature regarding minimal donor site morbidity and the excellent outcome observed in this case, the ITB graft has potential to be a viable tissue for reconstruction of pectoralis major tendon ruptures.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 81%
“…Limitations of autograft tissue include a reduced survivorship of 70% at 5 years and 61% at 10 years, with a mean survival time of 9 years with revision or THA as the endpoint. Nine percent of the hips underwent revision arthroscopy and 27% underwent THA [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Philippon et al . [ 27 ] concluded that segmental labral reconstruction with an iliotibial band autograft yield excellent results and high patient satisfaction at 10-year follow-up. Labral reconstruction, even in the context of severe chondral damage, has shown favorable results.…”
Section: Discussionmentioning
confidence: 99%
“…Proponents of the segmental technique argue that healthy labra native tissue can be unnecessarily sacrificed. Additionally, most of the available outcomes data on reconstruction, even in the long-term follow-up, comes from the segmental alternative [ 26 , 27 ]. In the circumferential or total labral reconstruction, the whole native labrum is taken down and reconstructed with the graft ( Fig.…”
Section: Segmental and Circumferential Labral Reconstructionmentioning
confidence: 99%